Controls on boreal peat combustion and resulting emissions of carbon and mercury. (28th February 2018) - Kohlenberg, Andrew J; Turetsky, Merritt R; Thompson, Dan K; Branfireun, Brian A; Mitchell, Carl P J
Abstract: Warming in the boreal forest region has already led to changes in the fire regime. This may result in increasing fire frequency or severity in peatlands, which could cause these ecosystems to shift from a net sink of carbon (C) to a net source of C to the atmosphere. Similar to C cycling, peatlands serve as a net sink for mercury (Hg), which binds strongly to organic matter and accumulates in peat over time. This stored Hg is also susceptible to re-release to the atmosphere during peat fires. Here we investigate the physical properties that influence depth of burn in experimental peat columns and the resulting emissions of CO, CO2, CH4, and gaseous and particulate Hg. As expected, bulk density and soil moisture content were important controls on depth of burn, CO2 emissions, and CO emissions. However, our results show that CH4 and Hg emissions are insensitive to combustion temperature or fuel moisture content. Emissions during the burning of peat, across a wide range of moisture conditions, were associated with low particulate Hg and high gaseous Hg release. Due to strong correlations between total Hg and CO emissions and because high Hg emissions occurred despite incomplete combustion of total C, our results suggest that Hg release during peat burning is governed by the thermodynamics of Hg reduction more so than by the release of Hg associated with peat combustion. Our measured emissions ratios, particularly for CH4 :CO2, are higher than values typically used in the upscaling of boreal forest or peatland fire emissions. These emission ratios have important implications not only for our understanding of smouldering chemistry, but also for potential influences of peat fires on the Earth's climate system.